Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I ran across a cool series I have been trying to chip away at.

$$\sum_{k=1}^{\infty}\frac{\zeta(2k+1)-1}{k+2}=\frac{-\gamma}{2}-6\ln(A)+\ln(2)+\frac{7}{6}\approx 0.0786\ldots$$

where A = the Glaisher-Kinkelin constant. Numerically, it is approx. $1.282427\ldots$

I began by writing zeta as a sum and switching the summation order

$$\sum_{n=2}^\infty \sum_{k=1}^\infty \frac{1}{(k+2)n^{2k+1}}$$

The first sum is the series for $-n^3\ln(1-\frac{1}{n^2})-n-\frac{1}{2n}$

So, we have $-\sum_{n=2}^\infty \left[\ln(1-\frac{1}{n^2})+n+\frac{1}{2n}\right]$

This series numerically checks out, so I am onto something. At first glance the series looks like it should diverge, but it does converge.

Another idea I had was to write out the series of the series:

$$1/3(1/2)^{3}+1/4(1/2)^{5}+1/5(1/2)^{7}+\cdots +1/3(1/3)^{3}+1/4(1/3)^{5}+1/5(1/3)^{7}+\cdots +1/3(1/4)^{3}+1/4(1/4)^{5}+1/5(1/4)^{7}+\cdots$$

and so on.

This can be written as $$1/3x^{3}+1/4x^{5}+1/5x^{7}+\cdots +1/3x^{3}+1/4x^{5}+1/5x^{7}+\cdots + 1/3x^{3}+1/4x^{5}+1/5x^{7}+\cdots $$

where $x=1/2,1/3,1/4,\ldots$

This leads to the series representation for:

$$\frac{-\ln(1-x^2)}{x^3}-\frac{1}{x}-\frac{x}{2}$$

Since $x$ is of the form $1/n$, we end up with the same series as before.

Now, my quandary. How to finish?. Where in the world does that Glaisher-Kinkelin constant come in, and how can that nice closed from be obtained?. Whether from the series I have above or some other means. As usual, it is probably something I should be seeing but don't at the moment.

The GK constant has a closed form of $$e^{\frac{1}{12}-\zeta^{'}(-1)}$$.

Which means an equivalent closed form would be $\frac{-\gamma}{2}+\ln(2)+6\zeta^{'}(-1)+\frac{2}{3}$

Thanks all.

share|improve this question
add comment

1 Answer 1

up vote 8 down vote accepted

We have $$ \begin{eqnarray*} &&\sum_{n=2}^\infty\left( -n^3\log(1-\frac{1}{n^2})-n-\frac{1}{2n}\right)\\ &=&\lim_{N\to\infty}\sum_{n=2}^N\left( -n^3\log(1-\frac{1}{n^2})-n-\frac{1}{2n}\right)\\ &=&\lim_{N\to\infty}\left(\sum_{n=2}^N -n^3\log(1-\frac{1}{n^2})-\left(\frac{N^2+N-2}{2}\right)-\left(\frac{\log(N)}{2}-\frac{1}{2}+\frac{\gamma}{2}+O\left(\frac{1}{N}\right)\right)\right)\\ &=&\lim_{N\to\infty}[\sum_{n=2}^N (2n^3\log(n)-n^3\log(n+1)-n^3\log(n-1))-\left(\frac{N^2+N-2}{2}\right)-\left(\frac{\log(N)}{2}-\frac{1}{2}+\frac{\gamma}{2}\right)] \end{eqnarray*} $$ In the sum on the last line, we may gather together the coefficients of each logarithm (terms at the boundary of the sum are a little funny), giving $$ \begin{eqnarray*} &&\lim_{N\to\infty}[\sum_{n=2}^N(-6n\log(n))+\log(2)+(N^3+3N^2+3N+1)\log(N)-N^3\log(N+1)-\left(\frac{N^2+N-2}{2}\right)-\left(\frac{\log(N)}{2}-\frac{1}{2}+\frac{\gamma}{2}\right)]\\ &=&\lim_{N\to\infty}[\sum_{n=2}^N(-6n\log(n))+\log(2)-N^3\log\left(1+\frac{1}{N}\right)+(3N^2+3N+1)\log(N)-\left(\frac{N^2+N-2}{2}\right)-\left(\frac{\log(N)}{2}-\frac{1}{2}+\frac{\gamma}{2}\right)]\\ &=&\lim_{N\to\infty}[\sum_{n=2}^N(-6n\log(n))+\log(2)-N^3\left(\frac{1}{N}-\frac{1}{2N^2}+\frac{1}{3N^3}+O\left(\frac{1}{N^4}\right)\right)+(3N^2+3N+1)\log(N)-\left(\frac{N^2+N-2}{2}\right)-\left(\frac{\log(N)}{2}-\frac{1}{2}+\frac{\gamma}{2}\right)]\\ &=&\lim_{N\to\infty}[\sum_{n=2}^N(-6n\log(n))+\left(3N^2+3N+\frac{1}{2}\right)\log(N)+\left(\frac{-3}{2}N^2+\frac{7}{6}-\frac{\gamma}{2}+\log(2)\right)]\\ &=&-6\log\left(\lim_{N\to\infty}\left(\frac{\prod_{n=1}^N n^n}{N^{N^2/2+N/2+1/12}e^{-N^2/4}}\right)\right)+\frac{7}{6}-\frac{\gamma}{2}+\log(2)\\ &=&-6\log(A)+\frac{7}{6}-\frac{\gamma}{2}+\log(2) \end{eqnarray*} $$ Here, I am taking $$ A=\lim_{N\to\infty}\frac{\prod_{n=1}^N n^n}{N^{N^2/2+N/2+1/12}e^{-N^2/4}} $$ as the definition of the Glaisher-Kinkelin constant.

share|improve this answer
    
Wow, thanks pink elephants. No wonder I did not finish it:). Thanks a lot. –  Cody Jul 24 '12 at 15:24
    
Pink elephants, may I ask another question?. I appreciate your fine response. I follow all of it except for how you got from $\lim_{N\to \infty}\left[\sum_{n=2}^{N}(-2n^{3}\log(n)+n^{3}\log(n+1)+n^{3}\log(n-1))\right]‌​$ to $\lim_{N\to \infty}\left[\sum_{n=2}^{N}(-6\log(n))+\log(2)+(N+1)^{3}\log(N)-N^{3}\log(N+1) \right]$. The part where you mention gathering the coefficients of the logs. Thanks. –  Cody Jul 24 '12 at 18:32
    
@Cody: Suppose $2\leq j\leq N-1$. I want to see what the coefficient of $\log(j)$ in this sum is. We get a contribution of $-2j^3$ from the first term when $n=j$, a contribution of $(j-1)^3$ from the second term when $n=j-1$, and a contribution of $(j+1)^3$ from the third term when $n=j+1$. In total, then, the coefficient of $\log(j)$ is $-2j^3+(j-1)^3+(j+1)^3=6j$ (hmm...above, I said that the coefficient was $-6j$. Maybe this is a mistake?). The coefficients of $\log(2)$, $\log(N)$, and $\log(N+1)$ are a little different, as there are fewer values of $n$ in the summation which contribute. –  Julian Rosen Jul 24 '12 at 19:01
    
@Cody I just noticed that I dropped that minus sign earlier. Fixing it now –  Julian Rosen Jul 24 '12 at 19:02
    
Thanks a lot PE fore the fast response. I was playing around with it by writing out terms and I see what you mean. It was kind of rough to see (at least for me) at first. The whole thing is clever and cool. I see where the 6n and log(2) came from. It was the other two terms I did not see right off. Thanks a bunch. –  Cody Jul 24 '12 at 19:19
show 3 more comments

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.